Modeling the inhomogeneous lithium plating in lithium-ion batteries induced by non-uniform temperature distribution. (1st September 2022) - Sun, Tao; Shen, Tengteng; Zheng, Yuejiu; Ren, Dongsheng; Zhu, Wenkuan; Li, Jian; Wang, Yuan; Kuang, Ke; Rui, Xinyu; Wang, Shan; Wang, Li; Han, Xuebing; et al.
Abstract: Under fast-charging or low-temperature charging conditions, large-format lithium-ion batteries are prone to inhomogeneous lithium plating, resulting in localized degradation and even internal short circuit, thus requiring a thorough investigation. This study establishes a three-dimensional electrochemical model to analyze the inhomogeneous lithium plating behavior in lithium-ion batteries. The model is validated with the voltage profiles and temperature distributions of a 24Ah pouch lithium-ion battery during low-temperature charging. The inhomogeneous lithium plating induced by non-uniform temperature distribution and the underlying mechanism are investigated using the model. The local current density and overpotential turn out to be the key factors affecting the spatial distribution of plated lithium. Moreover, the effects of temperature gradients on the lithium plating and stripping behaviors are explored. In-plane temperature gradient shows little effect on the total amount of plated lithium, but leads to apparent inhomogeneity in the distribution of plated lithium, with the differences between the concentrations of plated lithium in the upper and lower half of battery reach 57.61%, 103.06% and 159.68% of the average concentration in the whole battery during 1C charging at -5, 5 and 10°C, respectively. The temperature gradient also significantly influences the battery voltage relaxation profile related to the lithium stripping process. The characteristic plateau in the battery voltage relaxation profile disappears when the temperature gradient increases to larger than 6°C, leading to difficulty in detecting inhomogeneous lithium plating in large-format lithium batteries. The results presented in this study can provide helpful guidance for the design and management of large-format lithium-ion batteries. Graphical abstract: Image, graphical abstract